Secret invasion: inhumans ebook - Pokaski, Joe (Secret Invasion: Inhumans (2008)., 2015)
Collects Secret Invasion: Inhumans #1-4. Spinning directly out of SECRET INVASION - the hunt for Black Bolt begins! Blackbolt was replaced by the Skrulls, now it's time to find out if the Inhumans' former king is dead or alive! How will the loss of their leader tear apart the Royal Family? Can the mighty monarch recover from this personal blow - that is, if he's even still living? And how far will Medusa, Crystal, Triton, Karnak, and Gorgon go to find their disposed king?